Game-Based Learning and Students’ Behavioral Engagement at a Private School in Minahasa Utara - Kondo, Petrus; Tamalea, Violina Gloria Glenny Ruth (DIDASCO, 2023)
This study was to determine the correlation between Game-based learning and Students behavioral engagement. This study used quantitative design method which were descriptive and correlational. The instrument used in this study is questionnaire. The researchers adapted the questionnaire from Kolengen (2012) for Game-based learning and second questionnaire adapted from Setyowati (2021) for Student behavioral engagement. The respondents of this study were 65 students from grades VII C and VII D of SMP Advent Unklab. The result of this study showed that the level of used Game-based learning was 4.00 which is categorized in high level. Secondly, the level of Student behavioral engagement was 3.91 which is high level. The last result showed that there is significant correlation between Game-based learning and Student behavioral engagement.